Educational Policy, Power, and Gender Inequality in Afghan Secondary Education under Taliban Rule - Bibi Zainab Nasiri (Journal of Asian Social Science Research, 2026)
Abstract Since the Taliban’s return to power in 2021, restrictions on girls’ secondary education in Afghanistan have intensified gender inequality and reinforced political control. Although existing studies document these restrictions, less attention has been given to how education policy operates as a mechanism of patriarchal authority and how affected communities respond. This study examines how current policies restrict girls’ access to secondary schooling, shape their experiences, and sustain wider structures of gendered power. Using a qualitative design, it draws on interviews with female students and teachers from four Afghan provinces, supported by policy documents, NGO reports, and academic literature. The findings indicate that educational exclusion is legitimized through religious and cultural narratives that strengthen male-dominated authority. Participants reported psychological distress, diminished aspirations, unequal treatment, curriculum limitations, and exclusion from decision-making. At the same time, girls, teachers, families, and reform-oriented actors pursued online learning, underground schools, female-led learning spaces, and advocacy framing girls’ education as both an Islamic and human right. The study contributes to debates on gender, education, and authoritarian power by showing how schooling can function as social control. It concludes that restoring access requires inclusive policy reform, protection for alternative learning, and women’s participation in educational governance.